Transcriptome and Metabolome Analyses Reveal the Involvement of Multiple Pathways in Flowering Intensity in Mango - Liang, Qingzhi; Song, Kanghua; Lu, Mingsheng; Dai, Tao; Yang, Jie; Wan, Jiaxin; Li, Li; Chen, Jingjing; Zhan, Rulin; Wang, Songbiao (Frontiers in Plant Science, 2022)
Mango (Mangifera indica L.) is famous for its sweet flavor and aroma. China is one of the major mango-producing countries. Mango is known for variations in flowering intensity that impacts fruit yield and farmers' profitability. In the present study, transcriptome and metabolome analyses of three cultivars with different flowering intensities were performed to preliminarily elucidate their regulatory mechanisms. The transcriptome profiling identified 36,242 genes. The major observation was the differential expression patterns of 334 flowering-related genes among the three mango varieties. The metabolome profiling detected 1,023 metabolites that were grouped into 11 compound classes. Our results show that the interplay of the FLOWERING LOCUS T and CONSTANS together with their upstream/downstream regulators/repressors modulate flowering robustness. We found that both gibberellins and auxins are associated with the flowering intensities of studied mango varieties. Finally, we discuss the roles of sugar biosynthesis and ambient temperature pathways in mango flowering. Overall, this study presents multiple pathways that can be manipulated in mango trees regarding flowering robustness.